Profile of Some Cytokines in Sera of Children with Autism Syndrome - M. Halboot, Kamil; K.Melconian, Alice; AL- Saffar, Jenan (Iraqi Journal of Science, 2023)
Autism spectrum disorder (ASD) is a spectrum of behavioral anomaliescharacterized by impairment in social interactions and communication deficits. Apotential role for immune dysfunction has been suggested in ASD. To test thishypothesis, certain cytokines: IL-2, IL-10, IL-12, IL-17A and IFN-γ wereinvestigated in serum of all participants. The study includes: 39 child (male andfemale) aged < 5 to10 years with confirmed diagnosis of autism using standardassessment, age and gender matched 24 confirmed healthy children and 19 nonautistic siblings used as controls. Serum was isolated and cytokines were detectedusing enzyme linked immunosorbent assay (ELISA). The observations indicate asignificant increase (P < 0.05) in autistic patients serum levels of IL-10 comparedwith healthy control, but with lack of significant difference with their related nonautistic siblings. Whereas detection of IL-12 and IFN-γ in the autistic patients serumshowed significantly decrease level (P < 0.05) compared with healthy control, butwith lack of significant difference with their related non autistic siblings. On theother hand, detection of IL-2 and IL-17A results showed no significant (P > 0.05)differences compared with healthy control and non autistic siblings.